Training Certified Risk Associates for Internal Supervisory in ponegoro University Semarang - Tanti Widia Nurdiani; R. M Mahrus Alie (PT FORMOSA CENDEKIA GLOBAL, 2022)
To enhance good business governance practices, leaders and employees must meet the minimum requirements and competency standards and be knowledgeable about risk management for agency activities. Thus, CRA certification is a competency-based training program for mid-level risk management practitioners in order to address existing issues. As a form of community empowerment, Smart Indonesia Academy provides training and certification in risk management to the team of the Diponegoro University Internal Monitoring Unit. This study aims to investigate the community service activities provided by the Smart Indonesia Academy by providing risk management training and certification to the team of the Diponegoro University Internal Oversight Unit. The analytic-descriptive method was utilized to collect data, analyze it, and interpret the results of this qualitative study. The findings of the study indicate that Smart Indonesia Academy has been successful in empowering the community through CRA training and certification that is well-managed and effective. This program for community service is all-inclusive and can reach the goals set by the Chancellor of Diponegoro University.